The cyberwar mirage and the utility of cyberattacks in war: How to make real use of Clausewitz in the age of cyberspace - Jeppe Teglskov Jacobsen (Danish Institute for International Studies (DIIS), 2014)
Cyberwar is everywhere - in the media, in the military, among politicians and in academia. It is the new weapon of mass discussion. But there is no such thing as cyberwar. This observation, however, does not render cyberattacks unimportant. The article revisits the debate on Carl von Clausewitz's On War (1832), and examines the utility of cyberattacks as a tool in future war. In doing so, the article not only targets the misunderstandings and exaggerations prevalent in the literature, but demonstrates that Clausewitz's On War, albeit being two centuries old, is a valuable analytical lens in making sense of the relationship between cyberattacks and war. Drawing on the Clauzewitzian trinity, the article finds that cyberattacks can be useful tools in warfare, particularly in the initial stages of war. They are easily deployable and have already proven capable of causing physical damage. However, the article argues that cyberattacks remain inferior to conventional military weaponry, ultimately rendering cyberwar - understood as a war fought primarily through cyberspace - unlikely.
Keywords: 300